PENGARUH SISTEM INTERAKSI SOSIAL TERHADAP PERKEMBANGAN KARAKTER TOKOH KURONUMA SAWAKO DALM FILM KIMI NI TODOKE KARYA SUTRADARA KUMAZAWA NAOTO - VERAWATI, ADHITYA RULLY (Fakultas Ilmu Budaya Universitas Brawijaya, 2013)
ABSTRACT Literature has close related with people to presenting social issues. Film as one of the study of literature has the ability to 'present' of life to show social problems that occured in community. It is reflected in Kimi Ni Todoke movies. This film tells about a girl named Sawako Kuronuma who are victims of ijime, but she always trying to do good things for peoples around her every day. Through social interaction, the authors find the factors that influence the characters development of Sawako Kuronuma. To analyze the character development, authors use a sociological approach that focused on social interaction system conducted by characters with the surrounding environment. The author also uses mise-en-scene’s theory in order to get deep analysis of the movies. As the results, Sawako’s character is grows by social interaction process. She blend with the previous socially isolating group and also, she managed to have a group and close friends named Yano and Yoshida, who make her have courages to express what she feels. For subsequent studies using this film as research data, the authors suggest to use psychoanalytic approach to enrich literature appreciation. Keyword : Movies, character development, social interaction